PENGARUH AI DI MEDIA SOSIAL TERHADAP PENYEBARAN HOAKS DAN PERSEPSI KEPERCAYAAN MAHASISWA PROGRAM STUDI KOMPUTERISASI AKUNTANSI UNIVERSITAS SRIWIJAYA - Adelitan Salsabilah Amir; Berlian Wanna; Novela Artika Sari Devi (Jurnal Riset Teknik Komputer, 2026)
The rapid advancement of Artificial Intelligence (AI) on social media platforms has significantly shaped the way users receive and evaluate information. This study aims to analyze the impact of AI exposure on social media regarding hoax dissemination and the information trust perception of students in the Computerized Accounting Study Program at Sriwijaya University. A quantitative approach was employed through a survey method using a five-point Likert scale questionnaire distributed to 58 respondents selected through simple random sampling from a population of 136 active students. Data were analyzed through multiple linear regression using SPSS software. The final research instrument was confirmed to be valid through a three-stage validity testing process and was found to be reliable. The classical assumption tests indicated that the regression model met the requirements of normality, absence of multicollinearity, and homoscedasticity. The analysis revealed that both AI exposure and hoax dissemination have a positive and significant influence on students’ information trust perception, with hoax dissemination demonstrating a stronger effect. Furthermore, the coefficient of determination showed that 77.4% of the variation in students’ trust perception could be explained by the two independent variables. These findings highlight the urgent need for universities to integrate digital literacy and AI literacy programs into the academic curriculum to reduce the negative effects of AI-driven misinformation and improve students’ ability to evaluate information critically.